THE DIFFICULT PATH OF THE SOUTHERN LEND-LEASE ROUTE FOR THE USSR: THE INSIDIOUS «NEUTRALITY» OF IRAN AND TURKEY - Alexander I. Shumilin (Научно-аналитический вестник Института Европы РАН)
In the last decades, the main aspects of the interaction of the allies of the anti-Hitler coalition on the basis of Lend-Lease in the northern seas (in particular, the functioning of the northern route for the delivery of weapons, materials and products to the ports of Murmansk and Arkhangelsk) have been studied quite comprehensively and deeply in Soviet historiography. This can be largely explained by the fact that the passage of American-British convoys by this route was often accompanied by active combat clashes with the ships of the surface and submarine fleets of Germany, which turned this route into a theater of military operations for the allies with a manifestation of genuine heroism on the part of the latter. Against this background, Soviet researchers did not pay enough attention to the alternative southern route – mainly through the Persian Gulf to Iran (then along the Caspian Sea to the ports of Azerbaijan), and later – through the Bosphorus and Dardanelles (to the port of Odessa). There were not many heroic battles with Hitler's satellites on these routes, but the success of the convoys was ensured mainly by the work of Soviet diplomats and intelligence officers, who overcame the political barriers erected by Berlin in Iran and Turkey under the cover of the formal neutrality of these countries. The author hopes to make a feasible contribution to the in-depth study of these episodes of the struggle of the USSR and its allies against the Third Reich, based on a number of new sources and documents.